Effect of organic and inorganic sources of nutrition on productivity and economics of tomato (Lycopersicum esculentum) in Varanasi (Current Horticulture, 2024)
A field experiment was conducted during winter season of 2016- 2017 to find out the effect of different organic and inorganic sources of nutrition on growth, productivity and economics of tomato cultivation in Varanasi region. The organic sources of fertilizer were farmyard manure (FYM), poultry manure (PM), vermicompost (VC) with three levels of each and one chemical fertilizer dose applied as 100% RDF of NPK. The chemical fertilizer (CF) was applied at recommended dose of 180:60:60 kg/ha of N:P2O5:K2O. The application of 10 t poultry manure/ ha recorded maximum growth and fruit yield (584.69 q/ha), which was significantly superior to its own lower levels of poultry manure and rest of organic manures as well as inorganically cultivated tomato crop, i.e. 100% RDF of NPK through chemical fertilizer. However, higher levels of each organic manure gave significantly higher growth and fruit yield. Lowest net return was observed with treatment (VC: 2.5, t vermicompost/ha). Crop alimentation of tomato by supplying 10 t PM/ha recorded highest benefit:cost ratio (3.39) among organic sources. While, within organic and inorganic sources; application of RDF of NPK through chemical fertilizer recorded quite lesser benefit:cost ratio (3.36) than organically grown tomato.
Keywords: Tomato; Organic manures; FYM; PM; VC; Chemical fertilizer; Fruit yield; Economics